Pemikiran Immanuel Kant dan Implikasinya dalam Diskursus Pendidikan Akhlak - Abbad Arribaath Brimantyawan; Aabidah Ummu ‘Aziizah; Unik Hanifah Salsabila (Peneliti.net, 2022)
Kant's ethical formulation is supported by the objections of pure reason and practical ratio. Kant's introduction contains an a priori element due to this criticism of pure ratio. On the other hand, empiricism emphasizes the latter, stressing sensory knowledge. In terms of the praxis ratio, Kant's ethical axis is founded on free will, soul immortality, and the existence of God. Meeting the soul's immortality in humans entails making commitments that need either good or bad actions. Kant's fundamental ethical grounding is his deontological theory of regulation or idea of obligation, which emphasizes good deeds as obligations and ill deeds as prohibitions without regard for impact. Kant's ethics and moral education are both deontological. Kant's ethics and moral education all affirm the freedom of choice, the immortality of the soul, and the reality of God. Kant guessed but did not discover the Essence in the transcendental dimension, whereas moral education began with the Essence's meaning. Kant's ethics not being widely regarded as human ethical norms, categorical imperatives have not been adequately grounded in moral practice.